An O2-sensing diguanylate cyclase broadly affects the aerobic transcriptome in the phytopathogen Pectobacterium carotovorum - Fekete, Florian J.; Marotta, Nick J.; Liu, Xuanyu; Weinert, Emily E. (Frontiers in Microbiology, 2023)
Pectobacterium carotovorum is an important plant pathogen responsible for the destruction of crops through bacterial soft rot, which is modulated by oxygen (O2) concentration. A soluble globin coupled sensor protein, Pcc DgcO (also referred to as PccGCS) is one way through which P. carotovorum senses oxygen. DgcO contains a diguanylate cyclase output domain producing c-di-GMP. Synthesis of the bacterial second messenger c-di-GMP is increased upon oxygen binding to the sensory globin domain. This work seeks to understand regulation of function by DgcO at the transcript level. RNA sequencing and differential expression analysis revealed that the deletion of DgcO only affects transcript levels in cells grown under aerobic conditions. Differential expression analysis showed that DgcO deletion alters transcript levels for metal transporters. These results, followed by inductively coupled plasma -mass spectrometry showing decreased concentrations of six biologically relevant metals upon DgcO deletion, provide evidence that a globin coupled sensor can affect cellular metal content. These findings improve the understanding of the transcript level control of O2-dependent phenotypes in an important phytopathogen and establish a basis for further studies on c-di-GMP-dependent functions in P. carotovorum.